Abiding Dreams - Jaja, Sasi Miet (Literamed Publications Nigeria Ltd, 2011)
Jasper comes with a passion and flair that shoots him into instant fame.His first play at junior secondary school earns his school a national award.Consequently,he finds a haven in Theatre Arts,but his father insists he must be a medical doctor.Where does his sympathy swing:his passion and talent or his fathers choice of career?
Keywords: Fiction; Juvenile Literature